Molecular and Microbiological Insights on the Enrichment Procedures for the Isolation of Petroleum Degrading Bacteria and Fungi - Spini, Giulia; Spina, Federica; Poli, Anna; Blieux, Anne-Laure; Regnier, Tiffanie; Gramellini, Carla; Varese, Giovanna C.; Puglisi, Edoardo (Frontiers in Microbiology, 2018)
Autochthonous bioaugmentation, by exploiting the indigenous microorganisms of the contaminated environment to be treated, can represent a successful bioremediation strategy. In this perspective, we have assessed by molecular methods the evolution of bacterial and fungal communities during the selective enrichment on different pollutants of a soil strongly polluted by mixtures of aliphatic and polycyclic hydrocarbons. Three consecutive enrichments were carried out on soil samples from different soil depths (0-1 m, 1-2 m, 2-3 m), and analysed at each step by means of high-throughput sequencing (HTS) of bacterial and fungal amplicons biomarkers. At the end of the enrichments, bacterial and fungal contaminants degrading strains were isolated and identified in order to i) compare the composition of enriched communities by culture-dependent and culture-independent molecular methods and to ii) obtain a collection of hydrocarbon degrading microorganisms potentially exploitable for soil bioremediation. The molecular results highlighted that for both bacteria and fungi the pollutant type had a partial shaping effect on the enriched communities, whereas on the contrary neither the soil depth or the enrichment step had significant effects on the composition of the final microbial communities. Molecular analyses were quite well in agreement with culture-dependent analyses in terms of most abundant microbial genera. A total of 95 bacterial and 94 fungal strains were isolated after selective enrichment procedure on different pollutants. On the whole, isolated bacteria where ascribed to manly Pseudomonas genus followed by Sphingobacterium, Bacillus, Stenothrophomonas, Achromobacter and Serratia. For the fungal isolates, Fusarium was the most abundant genus followed by Trichoderma and Aspergillus. The microbial species comprising more isolates, such as P. putida, A. xylosoxidans and O. anthropi for bacteria, F. oxysporum and F. solani for fungi, were also the dominant OTUs assessed in Illumina.